Diversity of Oral Microbiome of Women From Urban and Rural Areas of Indonesia: A Pilot Study - Widyarman, Armelia Sari; Theodorea, Citra Fragrantia; Udawatte, Nadeeka S.; Drestia, Aradhea Monica; Bachtiar, Endang W.; Astoeti, Tri Erri; Bachtiar, Boy M. (Frontiers in Oral Health, 2021)
Objective: The studies on the influence of geographical and socio-economic factors on the oral microbiome remain underrepresented. The Indonesia basic health research (RISKESDAS) 2018, showed an increasing trend in non-communicable diseases compared with the previous report in 2013. The prevalence of diabetes, heart disease, hypertension, and obesity are reported to be higher in urban areas than in rural areas. Interestingly, non-communicable diseases were found to be more prevalent in women than men. This pilot study aimed to examine the oral health and oral microbiome derived from tongue samples of healthy Indonesian women from urban and rural areas. Methods: Twenty women aged 21–47 years old from West Jakarta, residents of DKI Jakarta (n = 10) as representative of the urban area, and residents of Ende, Nangapanda, East Nusa Tenggara (n = 10) as representative of the rural area were recruited for this pilot study. The participants were evaluated by the Simplified Oral Hygiene Index (OHI-S) according to the criteria of Greene and Vermillion and divided into three groups. High-throughput DNA sequencing was performed on an Illumina iSeq 100 platform. Results: The principal component analysis displayed a marked difference in the bacterial community profiles between the urban and rural localities. The presence of manifest was associated with increased diversity and an altered oral bacterial community profile in the urban women. Two bacterial taxa were present at significantly higher levels (adjusted p < 0.01) in the urban oral microflora (Genus Prevotella and Leptotricia) could account for this difference irrespective of the individual oral hygiene status. The linear discriminant analysis effect size (LEfSe) analysis revealed several distinct urban biomarkers. At the species level, Leptotrichia wadei, Prevotella melaninogenica, Prevotella jejuni, and P. histicola, show an excellent discriminatory potential for distinguishing the oral microflora in women between urban and rural areas. Further, using SparCC co-occurrence network analysis, the co-occurrence pattern in the dominant core oral microbiome assembly was observed to be specific to its ecological niche between two populations. Conclusions: This is the first pilot study demonstrating the characterization of the oral microbiome in Indonesian women in urban and rural areas. We found that the oral microbiome in women displays distinct patterns consistent with geographic locality. The specific characterization of the microbiota of Indonesian women is likely linked to geographical specific dietary habits, cultural habits, and socio-economic status or the population studied.